Nanosilica incorporated coarse wool-epoxy hybrid biocomposites with improved physico-mechanical properties - Jose, Seiko; George, Jesiya Susan; Jacob, Tinu Ann; Vijayan P, Poornima; Bhanu A. V., Asha; Nedumpillil, Namitha Nandanan; Thomas, Sabu (Frontiers in Materials, 2023)
In the reported work, the wool fabric was coated with epoxy resin by hand layup method to fabricate the wool-epoxy composite. Hydrophobic nanosilica was used as a filler to improve the mechanical characteristics. The physico-mechanical properties of the composites were analyzed using various analytical techniques. The surface morphology was examined with the aid of Scanning Electron Microscope. The biodegradability of the developed composites was determined by soil burial test. The presence of nanosilica in the composite was confirmed by Fourier Transform Infrared Spectroscopy. According to the findings, adding up to 0.5% nanosilica significantly increases the tensile and impact strength of the wool-epoxy composite. The contact angle measurement showed a slight enhancement in the hydrophobic properties of the composites due to the dispersion of hydrophobic nanosilica particles. The presence of nanosilica slightly reduced the water diffusivity in wool-epoxy-nanosilica composites when compared to wool-epoxy composites. The SEM images detected nanosilica inside the composites. After soil burial test, all the composites showed a weight reduction below 1.0%.